1994
DOI: 10.1101/gad.8.6.732
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of HOX protein function depends on DNA-protein and protein-protein interactions, both mediated by the homeo domain.

Abstract: [Key Words: Homeo box; homeo domain; transcriptional regulation; DNA-protein interaction; protein-protein interaction]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
118
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(120 citation statements)
references
References 46 publications
2
118
0
Order By: Relevance
“…The functional role of the N-terminal region of homeobox proteins is largely unknown. However, Zappavigna et al 34 reported the first evidence that sequences in the N-terminal region of a HOX protein influence transcriptional activity. Interestingly, we found one patient showing overexpression of both HOXA10 and HOXA10b, which revealed a triplication of HOXA and TCRb flanking clones with deletion of the distal clones on a ring chromosome 7.…”
Section: Discussionmentioning
confidence: 99%
“…The functional role of the N-terminal region of homeobox proteins is largely unknown. However, Zappavigna et al 34 reported the first evidence that sequences in the N-terminal region of a HOX protein influence transcriptional activity. Interestingly, we found one patient showing overexpression of both HOXA10 and HOXA10b, which revealed a triplication of HOXA and TCRb flanking clones with deletion of the distal clones on a ring chromosome 7.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the existence of other yet unidentified DNAbinding motifs within full-length HB9, which are critical for the interaction of HB9 target genes. The limited number of four genes we identified from the overlap of data sets from ChIP-onchip and gene expression analysis is a known phenomenon (38 -40) and is based on the various conditions, which are important for a specific modulation of target gene regulation (41,42). First, the gene expression is often controlled by cofactors recruited to the protein-DNA complexes as well as secondary or tertiary protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Six hundred micrograms of cell extract was immunoprecipitated with anti-HA antibody, anti-CDC6 antibody, or anti-HOXD13 antibody and detected by immunoblotting using anti-HA, anti-geminin, anti-CDC6, or anti-Myc antibodies. Glutathione S-transferase (GST) pulldown assays were performed as described by Zappavigna et al (66). Bacterially produced GST-HOXD13HD fusion protein and GST were immobilized on a glutathione-Sepharose 4B resin (Amersham).…”
Section: Vol 29 2009mentioning
confidence: 99%